Positive electrode for secondary battery and method for manufacturing the same, and secondary battery

JP7943549B2Active Publication Date: 2026-10-30PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023569451
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-23
Filing Date
2022-12-20
Publication Date
2026-10-30
Estimated Expiration
2042-12-20

AI Technical Summary

Benefits of technology

【0010】 本開示によれば、室温での抵抗の増大を抑制しつつ、電池の内部短絡が発生したときの高温下での抵抗を増大させることができる。よって、高い安全性と良好な電池性能を両立することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007943549000003
    Figure 0007943549000003
  • Figure 0007943549000001
    Figure 0007943549000001
  • Figure 0007943549000002
    Figure 0007943549000002
Patent Text Reader

Abstract

A secondary battery positive electrode comprising a positive electrode collector and a positive electrode active material layer supported on the positive electrode collector, wherein the positive electrode active material layer contains active material particles, a binder, and a heat-decomposable additive, and the heat-decomposable additive contains an acetamidobenzoic acid.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure primarily relates to positive electrodes for secondary batteries. [Background technology]

[0002] As the energy density of a secondary battery increases, the need for improved safety is paramount. Reducing heat generation due to internal short circuits is particularly important. Even a small short circuit can cause the separator to melt due to Joule heating from the short-circuit current, forming a larger short circuit. As the short circuit expands and the short-circuit current increases, the battery temperature rises exponentially. The higher the energy density of a secondary battery, the greater the Joule heating caused by the short-circuit current.

[0003] Patent Document 1 describes a composite oxide having a layered crystalline structure and mainly composed of lithium and nickel, with the general formula: Li a Ni 1-b-c M1 b M2 c The powder has an elemental composition represented by O2, 0.95≦a≦1.05, 0.01≦b≦0.10, 0.10≦c≦0.20 (where M1 is one or more elements selected from Al, B, Y, Ce, Ti, Sn, V, Ta, Nb, W, Mo, and M2 is one or more elements selected from Co, Mn, Fe), and the compressed density when the powder is pressure-molded is 4.0 g / cm³. 3 The conductivity of the compacted powder at 25°C: σ is 5 × 10 -2 ≥σ ≥ 5 × 10 -4 We propose a positive electrode active material characterized by being within the range of [S / cm]. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2000-315502 [Overview of the project] [Problems that the invention aims to solve]

[0005] Patent Document 1 states that, according to the above-mentioned positive electrode active material, thermal stability in the charged state is improved, and even when the battery experiences an internal short circuit, Joule heating due to the short-circuit current is suppressed, making it easier to ensure safety.

[0006] However, when the conductivity of the compacted powder is controlled as in Patent Document 1, the battery as a whole becomes highly resistive, leading to a decrease in battery performance. Furthermore, Patent Document 1 is a solution specifically for composite oxides mainly composed of lithium and nickel, and therefore lacks general applicability. [Means for solving the problem]

[0007] One aspect of this disclosure relates to a positive electrode for a secondary battery, comprising a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector, wherein the positive electrode active material layer comprises active material particles, a binder, and a pyrolytic additive, the pyrolytic additive comprising acetamidobenzoic acid.

[0008] Another aspect of this disclosure relates to a secondary battery comprising a positive electrode, a negative electrode, a non-aqueous electrolyte, and a separator interposed between the positive electrode and the negative electrode.

[0009] A further aspect of this disclosure relates to a method for producing a positive electrode for a secondary battery, comprising the steps of: preparing a positive electrode slurry containing active material particles, a binder, a pyrolytic additive, and a dispersion medium; preparing a positive electrode current collector; applying the positive electrode slurry to the surface of the positive electrode current collector to form a coating film; drying the coating film to form an unrolled layer; and rolling the unrolled layer to form a positive electrode active material layer, wherein the pyrolytic additive contains acetamidobenzoic acid and the dispersion medium contains an organic solvent. [Effects of the Invention]

[0010] According to this disclosure, it is possible to increase the resistance at high temperatures when an internal short circuit occurs in the battery while suppressing the increase in resistance at room temperature. Therefore, it is possible to achieve both high safety and good battery performance.

[0011] While the novel features of the present invention are set forth in the appended claims, the present invention will be better understood from the following detailed description, taken in conjunction with the accompanying drawings, both as to its structure and content, together with other objects and features of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] [Figure 1] 1 is a longitudinal cross-sectional view schematically illustrating the internal structure of a secondary battery according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF EMBODIMENTS FOR IMPLEMENTING THE INVENTION

[0013] Hereinafter, embodiments of the positive electrode for a secondary battery and the secondary battery using the same according to the present disclosure will be described by way of examples, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values and materials may be illustrated, but other numerical values and materials may be applied as long as the effects of the present disclosure can be obtained. In this specification, the description "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read as "not less than numerical value A and not more than numerical value B". In the following description, when the lower limit and upper limit of numerical values relating to specific physical properties, conditions, etc. are illustrated, any one of the illustrated lower limits and any one of the illustrated upper limits can be arbitrarily combined as long as the lower limit does not exceed the upper limit. Further, the present disclosure encompasses combinations of the matters described in two or more claims arbitrarily selected from the plurality of claims described in the appended claims. That is, as long as no technical contradiction arises, the matters described in two or more claims arbitrarily selected from the plurality of claims described in the appended claims can be combined.

[0014] A. Positive Electrode for Secondary Battery A positive electrode for a secondary battery according to an embodiment of the present disclosure includes a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector. The positive electrode active material layer is formed on the surface of the positive electrode current collector.

[0015] [Positive Electrode Current Collector] The positive electrode current collector is composed of a sheet-like conductive material. As the positive electrode current collector, non-porous conductive substrates (such as metal foil) or porous conductive substrates (such as mesh, net, or perforated sheet) are used.

[0016] [Cathode active material layer] The positive electrode active material layer is supported on one or both surfaces of the positive electrode current collector. The positive electrode active material layer is usually a positive electrode mixture layer composed of a positive electrode mixture, and is in the form of a film or membrane. The positive electrode mixture contains active material particles (particles of positive electrode active material), a binder, and a thermally decomposable additive as essential components. The active material particles may contain lithium-containing transition metal oxides. The binder contains at least one selected from the group consisting of fluororesins and hydrogenated nitrile butadiene rubber. The thermally decomposable additive contains acetamidobenzoic acid.

[0017] Acetamidobenzoic acid has little effect on battery performance even when present in the positive electrode active material layer. Acetamidobenzoic acid may be in acid form, zwitterionic form, or salt form, where the proton of the COOH group is substituted with a cation. The cation may be an ammonium cation, a metal cation (Na, K, Li, etc.), etc. Acetamidobenzoic acid may be 3-acetamidobenzoic acid or 4-acetamidobenzoic acid, but 3-acetamidobenzoic acid is more preferable. The content of 3-acetamidobenzoic acid in the total amount of acetamidobenzoic acid is preferably 98% by mass or more, and may be 100%.

[0018] Pyrolytic additives decompose and block the conductive path when an internal short circuit occurs in the battery, the short-circuit current increases, and the battery temperature rises. In other words, pyrolytic additives hardly increase resistance at room temperature, but selectively increase the internal resistance of the battery at high temperatures. Acetamidobenzoic acid decomposes at temperatures of approximately 250°C or higher, so the internal resistance of the battery increases significantly before the battery temperature rises excessively. The mechanism by which the conductive path is blocked is not clear, but it is presumed that the thermal decomposition of the pyrolytic additive generates gas within the positive electrode active material layer, causing localized structural changes in the positive electrode active material layer and thus increasing resistance.

[0019] Acetamidobenzoic acid is considered to be compatible with binders containing at least one selected from the group consisting of fluororesins and hydrogenated nitrile butadiene rubber (H-NBR). Fluororesins and H-NBR dissolve in organic solvents (e.g., N-methyl-2-pyrrolidone) used as dispersion media when forming the positive electrode active material layer. Acetamidobenzoic acid also dissolves moderately in organic solvents used as dispersion media. Therefore, it is considered that acetamidobenzoic acid, moderately dissolved in the organic solvent as fine particles or aggregates, can be uniformly dispersed in the positive electrode active material layer together with the binder. Furthermore, acetamidobenzoic acid is considered stable and less likely to cause side reactions in the presence of organic solvents. Note that when water is used as the dispersion media for the positive electrode slurry, the water may degrade the positive electrode active material, leading to a decrease in capacity.

[0020] It is desirable that at least a portion of the pyrolytic additive exists in the positive electrode active material layer as particles with a particle size of 10 μm or larger. Here, "particle" is a concept that includes primary particles, secondary particles, and aggregates formed by the aggregation of these, and in addition to general particles or particles, it also includes concepts such as aggregation and agglomeration. The particle size (or diameter of the aggregate) can be considered as the diameter of an equivalent circle having the same area as the area enclosed by the contour of the particle (or aggregate) when observing a cross-sectional sample, as described later. When pyrolytic additives are included in the positive electrode active material layer at such a size, it is presumed that the local structural changes in the positive electrode active material layer due to the thermal decomposition of the pyrolytic additive will be large, and the resistance will increase more significantly. The particle size of the pyrolytic additive may be 20 μm or larger, or 30 μm or larger. Furthermore, the maximum particle size of the pyrolytic additive is preferably 100 μm or less, but may also be 60 μm or less, or 50 μm or less. If the maximum value falls within the above range, the impact on battery performance can be kept sufficiently small.

[0021] Particle size can be measured as follows: (1) Preparation of cross-sectional sample of the positive electrode First, the positive electrode to be measured is prepared. Next, the positive electrode active material layer and the positive electrode current collector are simultaneously cut along the thickness direction of the positive electrode to form a cross-section. At this time, a thermosetting resin may be filled into the positive electrode active material layer and cured. For example, a cross-sectional sample of the positive electrode is obtained by the CP (Cross-Section Polisher) method, FIB (Focused Ion Beam) method, etc.

[0022] The positive electrode to be measured is taken from a secondary battery with a depth of discharge (DOD) of 90% or more. Depth of discharge (DOD) is the ratio of the amount of discharged electricity to the amount of electricity the battery has in a fully charged state. Note that the amount of electricity charged when charging a battery from a completely discharged state (DOD=100%) to a fully charged state (SOC=100%, DOD=0%) corresponds to the rated capacity. The voltage of a fully charged battery corresponds to the charge termination voltage. The voltage of a completely discharged battery corresponds to the discharge termination voltage.

[0023] (2) Image of the cross-section of the positive electrode using a scanning electron microscope (SEM) Next, the cross-sectional sample is observed using a scanning electron microscope (SEM). The SEM observation is performed at a low magnification (e.g., 200x to 1000x). The SEM image is taken so that a region of 300 μm or more (preferably 400 μm or more) in the planar direction of the positive electrode active material layer is observed.

[0024] (3) Elemental analysis using electron beam microanalyzer (EPMA) Elemental analysis is performed using EPMA with SEM images of cross-sectional samples. By extracting components derived from pyrolytic additives (e.g., nitrogen) from the EPMA analysis data of the cross-sectional samples, a map of pyrolytic additives is obtained. The measurement conditions for nitrogen mapping are an acceleration voltage of 8.0 kV and an irradiation current of 1.0 × 10⁻¹⁰. -7 Let A be the threshold, which is 1 / 3 of the maximum count in the positive electrode active material layer. Pixels with a detection level above this threshold are considered to be locations where the pyrolytic additive is present. From the resulting map, the particles or aggregates of the pyrolytic additive are identified. The diameter of the equivalent circle having the same area as the identified particles or aggregates is defined as the particle size of the pyrolytic additive.

[0025] Particles (or aggregates) of the pyrolytic additive with a particle diameter of 10 μm or more should be observed at least once within a rectangular observation field defined by a length of 300 μm in the planar direction of the positive electrode active material layer × the thickness T of the positive electrode active material layer (or one side of the positive electrode active material layer if positive electrode active material layers are provided on both sides of the positive electrode current collector (hereinafter the same)), but it is desirable to observe five or more. The greater the number of pyrolytic additive particles with a particle diameter of 10 μm or more observed within the above observation field, the greater the effect of selectively increasing the internal resistance of the battery at high temperatures. The upper limit of the number of pyrolytic additive particles with a particle diameter of 10 μm or more observed within the above observation field is, for example, 40 or less. The above counts may also be the average value of the number of pyrolytic additive particles with a particle diameter of 10 μm or more counted in multiple (e.g., three or more) observation fields (300 μm × T).

[0026] Only a small amount of pyrolytic additive is needed to be included in the positive electrode active material layer. The content of acetamidobenzoic acid in the positive electrode active material layer may be, for example, 0.1% to 5% by mass, 0.3% to 3% by mass, or 0.5% to 2% by mass. Furthermore, as described above, when the cross-section of the positive electrode active material layer is analyzed with a scanning electron microscope and electron beam microanalyzer, the area where acetamidobenzoic acid is present may be, for example, 0.5% to 27% by area, 1% to 15% by area, or 3% to 10% by area in a rectangular observation field defined by the length of the positive electrode active material layer in the planar direction and the thickness T of the positive electrode active material layer. The acetamidobenzoic acid content at the above rates does not significantly affect the battery capacity. Furthermore, the acetamidobenzoic acid contained in the above-mentioned proportion can be uniformly dispersed within the positive electrode active material layer as particles or aggregates of the appropriate particle size as described above.

[0027] The pyrolytic additive may contain an acetic acid component. The acetic acid component has the effect of suppressing the sedimentation of the positive electrode mixture in the positive electrode slurry prepared when forming the positive electrode active material layer. The acetic acid component may be acetic acid (acid form) having an OH group, or a salt form in which the proton of the OH group is replaced with a cation. The cation may be an ammonium cation, a metal cation (Na, K, Li, etc.), etc. It is desirable that the acetic acid component is contained in a ratio of 500 μg to 5000 μg per gram of the pyrolytic additive or acetamidobenzoic acid. The amount of acetic acid component contained in the pyrolytic additive or acetamidobenzoic acid can be measured, for example, by peeling the positive electrode active material layer from the positive electrode, extracting acetamidobenzoic acid from the positive electrode active material layer with a solvent, and analyzing the solvent containing acetamidobenzoic acid by ion chromatography. N-methyl-2-pyrrolidone (NMP) may be used as the solvent.

[0028] It is desirable that the pyrolytic additive coats only a portion of the surface of the active material particles. Pyrolytic additives present on the surface of active material particles are thought to efficiently block conductive paths between active material particles, between active material particles and conductive materials, or between active material particles and the positive electrode current collector at high temperatures. For example, pyrolytic additives present on the surface of active material particles and interposed between them reduce contact between active material particles through changes in state such as gasification. On the other hand, if the pyrolytic additive coats only a portion of the surface of the active material particles and not the entire surface, the resistance to the battery reaction hardly increases.

[0029] The fact that the pyrolytic additive coats only a portion of the surface of the active material particles can be confirmed by elemental mapping using EPMA on SEM images of cross-sectional samples of the cathode obtained by the method described above.

[0030] It is desirable that pyrolytic additives (especially particulate pyrolytic additives, particularly particles with a diameter of 10 μm or more) are predominantly located on the outermost surface side (i.e., the separator side) of the positive electrode active material layer, rather than on the positive electrode current collector side. This is because internal short circuits in batteries often begin to expand on the separator side of the positive electrode active material layer. Internal short circuits occur, for example, when conductive foreign matter penetrates the separator. By predominantly distributing the pyrolytic additives on the separator side of the positive electrode active material layer, a high-resistance region can be formed on the separator side of the positive electrode active material layer in the initial stages after a short circuit occurs. Therefore, the expansion of the short-circuited area can be suppressed.

[0031] More specifically, when the thickness of the positive electrode active material layer is T, the probability of the presence of a pyrolytic additive Pb in the region of the positive electrode active material layer from the surface of the positive electrode current collector to 0.5T, and the probability of the presence of a pyrolytic additive Pt in the region of the positive electrode active material layer from 0.5T from the surface of the positive electrode current collector to the outermost surface (i.e., the separator-side surface of the positive electrode active material layer) must satisfy, for example, 1.35 ≤ Pt / Pb, and may also satisfy 1.5 ≤ Pt / Pb ≤ 40. Note that if Pt / Pb < 1.35, it cannot be said that the pyrolytic additive is substantially biased towards the outermost surface of the positive electrode active material layer compared to the positive electrode current collector side.

[0032] Hereinafter, the region of the positive electrode active material layer from the surface of the positive electrode current collector to 0.5T will be referred to as the "lower layer region," and the region of the positive electrode active material layer from 0.5T from the surface of the positive electrode current collector to the outermost surface will be referred to as the "upper layer region."

[0033] Pb and Pt can be measured by analyzing cross-sectional samples of the positive electrode obtained by the method described above using SEM and EPMA. Specifically, the area occupied by the pyrolytic additive in the lower and upper layers of the elemental map of pyrolytic additives obtained from the EPMA analysis data of the cross-sectional sample is measured. At this time, all pyrolytic additives are counted regardless of their particle size. The ratio of the area of ​​the pyrolytic additive to the area of ​​the lower and upper layers is then considered as Pb and Pt, respectively. Pb and Pt are measured in a rectangular observation field defined by a length of 300 μm in the plane direction of the positive electrode active material layer × the thickness T of the positive electrode active material layer. Pb and Pt may also be the average values ​​of Pb and Pt obtained from multiple (e.g., 3 or more) observation fields.

[0034] Preferably, when the thickness of the positive electrode active material layer is T, the probability of the presence of a pyrolytic additive Pb(q) in the region of the positive electrode active material layer from the surface of the positive electrode current collector up to 0.25T and the probability of the presence of a pyrolytic additive Pt(q) in the region of the positive electrode active material layer from a position of 0.75T from the surface of the positive electrode current collector to the outermost surface (i.e., the separator-side surface of the positive electrode active material layer) may satisfy 1.5 ≤ Pt(q) / Pb(q) ≤ 50.

[0035] <Manufacturing method for positive electrode> Next, an example of a method for manufacturing a positive electrode for a secondary battery according to the embodiment of this disclosure will be described. The manufacturing method comprises the steps of: (I) preparing a positive electrode slurry containing active material particles, a binder, a pyrolytic additive, and a dispersion medium; (II) preparing a positive electrode current collector; (III) applying the positive electrode slurry to the surface of the positive electrode current collector to form a coating film; (IV) drying the coating film to form an unrolled layer; and (V) rolling the unrolled layer to form a positive electrode active material layer.

[0036] (I) Slurry preparation step The positive electrode slurry is prepared by mixing a positive electrode mixture containing active material particles, a binder and a thermally decomposable additive with a liquid dispersion medium to disperse the positive electrode mixture in the dispersion medium. The positive electrode mixture may further contain other components (for example, a conductive material). As the liquid dispersion medium, an organic solvent having excellent affinity for both the binder and the thermally decomposable additive is used.

[0037] As the organic solvent, it is preferable to use N-methyl-2-pyrrolidone (NMP), but alcohols such as ethanol, ethers such as tetrahydrofuran, amides such as dimethylformamide, ketones such as cyclohexanone, and the like may also be used.

[0038] As the thermally decomposable additive, at least acetamidobenzoic acid is used. The acetamidobenzoic acid may be mixed with the dispersion medium in advance to partially dissolve it. For example, a dispersion of particulate acetamidobenzoic acid having an average particle diameter d1 (d1<D1) may be prepared by mixing particulate acetamidobenzoic acid having an average particle diameter D1 with the dispersion medium. Here, the average particle diameter refers to the median diameter (D 50 ) at which the cumulative volume is 50% in the volume-based particle size distribution obtained by a laser diffraction particle size distribution analyzer. The average particle diameter D1 is desirably 100 μm or less, and it is more desirable to use acetamidobenzoic acid that passes through a 100 μm mesh. The average particle diameter d1 is desirably 50 μm or less.

[0039] As a binder, at least one selected from the group consisting of fluororesins and hydrogenated nitrile butadiene rubber is used. Examples of fluororesins include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), and vinylidene fluoride-hexafluoropropylene copolymer. These are readily soluble in organic solvents and are suitable for use in combination with sulfamic acid. PVDF is preferred among these.

[0040] (II) Steps to prepare the positive electrode current collector As the positive electrode current collector, a sheet-like conductive material (such as metal foil, mesh, net, or perforated sheet) is used. Among these, metal foil is preferred. Examples of materials for the positive electrode current collector include stainless steel, aluminum, aluminum alloy, and titanium. The thickness of the positive electrode current collector is not particularly limited, but for example, it can be 1 to 50 μm, or 5 to 30 μm.

[0041] (III) Process of forming a coating film of the positive electrode slurry A coating film is formed by applying the positive electrode slurry to the surface of the positive electrode current collector. Examples of coating devices for the positive electrode slurry include bar coaters, gravure coaters, blade coaters, roll coaters, comma coaters, die coaters, and lip coaters.

[0042] In a positive electrode slurry applied to the surface of a positive electrode current collector, it is desirable that at least a portion of the pyrolytic additive exists in particulate form with a particle size of 10 μm or larger. This makes it easy to obtain a positive electrode active material layer containing pyrolytic additives with a particle size of 10 μm or larger. Furthermore, the pyrolytic additive makes it easier to coat only a portion of the surface of the active material particles.

[0043] (IV) Drying process of the coating film Next, the coating is dried, and the dispersion medium is volatilized to form an unrolled coating. By appropriately controlling the drying conditions, the pyrolytic additive can be migrated from the lower layer to the upper layer (i.e., from the positive electrode current collector side to the separator side) along with the dispersion medium. As a result, the pyrolytic additive becomes more unevenly distributed on the separator side of the positive electrode active material layer than on the positive electrode current collector side. For example, when drying the coating at temperatures of 150°C or higher, or even 200°C or higher, the pyrolytic additive tends to become unevenly distributed on the separator side of the positive electrode active material layer than on the positive electrode current collector side.

[0044] For example, when the thickness of the unrolled layer is T2, the probability P2b of the presence of a pyrolytic additive in the region from the surface of the positive electrode current collector of the unrolled layer up to 0.5T2, and the probability P2t of the presence of a pyrolytic additive in the region from 0.5T2 from the surface of the positive electrode current collector of the unrolled layer up to the outermost surface, may satisfy 1.35 ≤ P2t / P2b.

[0045] (V) Rolling process of the unrolled layer Next, the unrolled layer is rolled to form a positive electrode active material layer. The rolling conditions are not particularly limited, but the density of active material particles (positive electrode active material) in the positive electrode active material layer is, for example, 3.3 g / cm³. 3 More than 4.0g / cm 3 The following is the case: 3.5 g / cm³ 3 More than 4.0g / cm 3 The following is also acceptable.

[0046] Here, we have described a method for controlling P2t / P2b by controlling the drying conditions of the coating film, but this is not the only way to control P2t / P2b. For example, a positive electrode active material layer consisting of two or more layers with different concentrations of pyrolytic additives may be formed by laminating two or more positive electrode slurries.

[0047] B. Secondary battery The secondary battery according to the embodiment of this disclosure comprises a positive electrode, a negative electrode, a lithium-ion conductive electrolyte, and a separator interposed between the positive electrode and the negative electrode. The secondary battery may be a liquid-type secondary battery containing an electrolyte as the lithium-ion conductive electrolyte, and the electrolyte may be a non-aqueous electrolyte or an aqueous electrolyte. A gel electrolyte or solid electrolyte in which the electrolyte is held in a matrix material may be used. An all-solid-state secondary battery containing a solid electrolyte as the lithium-ion conductive electrolyte may also be used. Secondary batteries include lithium-ion secondary batteries that use a material that reversibly intercepts and releases lithium ions as the negative electrode active material, lithium secondary batteries in which lithium metal is deposited at the negative electrode during charging and the lithium metal dissolves during discharge, and solid batteries containing a gel electrolyte or a solid electrolyte.

[0048] The following will explain the composition of a secondary battery in detail, using a lithium-ion secondary battery as an example.

[0049] [Positive electrode] As the positive electrode, a positive electrode for secondary batteries having the characteristics described above is used. The positive electrode active material layer is composed of a positive electrode mixture. The positive electrode mixture contains, as essential components, active material particles (particles of positive electrode active material), a binder, and a thermally decomposable additive (at least acetamidebenzoic acid), and may also contain optional components. Optional components may include conductive materials, thickeners, etc.

[0050] The thickness of the positive electrode active material layer is not particularly limited, but may be, for example, 50 μm to 150 μm, or 75 μm to 125 μm. A single positive electrode active material layer may be formed by multiple layers having different morphologies. For example, two or more layers containing active material particles with different average particle sizes may be stacked, or two or more layers with different types or compositions of positive electrode active materials may be stacked.

[0051] The average particle diameter of the active material particles (particles of the positive electrode active material) is, for example, 3 μm to 30 μm, and may be 5 μm to 25 μm. Here, the average particle diameter is the median diameter (D) at which the cumulative volume accounts for 50% of the volume-based particle size distribution obtained by a laser diffraction particle size distribution analyzer. 50The active material particles can be separated and recovered from the positive electrode. For the measuring device, for example, the "LA-750" manufactured by HORIBA, Ltd. can be used.

[0052] The average particle diameter of the active material particles may also be measured from the cross-sectional sample of the positive electrode as described above. Alternatively, an SEM image of the cross-section may be taken so that 10 or more active material particles are observed, and the diameter of the equivalent circle having the same area as the cross-section of each of the 10 or more active material particles can be determined by image processing, and the average value of these values ​​may be used as the average particle diameter.

[0053] The positive electrode active material constituting the active material particles may include a lithium-containing transition metal oxide. From the viewpoint of increasing capacity, it is desirable that the lithium-containing transition metal oxide includes lithium nickel oxide (composite oxide N) which contains lithium and Ni and has a layered rock salt type crystal structure. The proportion of composite oxide N in the positive electrode active material is, for example, 70% by mass or more, may be 90% by mass or more, or 95% by mass or more. The proportion of Ni among the metal elements other than Li in the composite oxide N may be 50 atomic percent or more.

[0054] The composite oxide N is, for example, formula (1): Li α Ni x1 M1 x2 M2 (1-x1-x2) O 2+β It is expressed as follows: Here, element M1 is at least one selected from the group consisting of V, Co, and Mn. Element M2 is at least one selected from the group consisting of Mg, Al, Ca, Ti, Cu, Zn, and Nb. However, equation (1) satisfies 0.95 ≤ α ≤ 1.05, -0.05 ≤ β ≤ 0.05, 0.5 ≤ x1 < 1, 0 ≤ x2 ≤ 0.5, and 0 < 1 - x1 - x2 ≤ 0.5. α increases or decreases with charging and discharging.

[0055] The composite oxide N contains Ni and may also contain at least one element selected from the group consisting of Co, Mn, and Al as elements M1 and M2. Co, Mn, and Al contribute to stabilizing the crystal structure of the composite oxide N.

[0056] From the standpoint of reducing costs and increasing capacity, the proportion of Co among the metal elements other than Li in the composite oxide N is preferably 0 to 20 atomic percent, and more preferably 0 to 15 atomic percent.

[0057] The proportion of Mn in the metal elements other than Li may be 10 atomic percent or less, or 5 atomic percent or less. The proportion of Mn in the metal elements other than Li may be 1 atomic percent or more, or 3 atomic percent or more, or 5 atomic percent or more.

[0058] The proportion of Al among metal elements other than Li may be 10 atomic percent or less, or 5 atomic percent or less. The proportion of Al among metal elements other than Li may be 1 atomic percent or more, or 3 atomic percent or more, or 5 atomic percent or more.

[0059] The composite oxide N is, for example, formula (2):Li α Ni (1-y1-y2-y3-z) Co y1 Mn y2 Al y3 M z O 2+β It can be expressed as follows: Element M is an element other than Li, Ni, Co, Mn, Al, and oxygen, and may be at least one selected from the group consisting of Ti, Zr, Nb, Mo, W, Fe, Zn, B, Si, Mg, Ca, Sr, Sc, and Y. However, equation (2) satisfies 0.95≦α≦1.05, -0.05≦β≦0.05, 0≦y1≦0.1, 0≦y2≦0.1, 0≦y3≦0.1, and 0≦z≦0.10. 1-y1-y2-y3-z(=v), which represents the atomic ratio of Ni, is for example 0.8 or greater, may be 0.85 or greater, or 0.90 or greater, or 0.95 or greater. Also, v, which represents the atomic ratio of Ni, may be 0.98 or less, or 0.95 or less.

[0060] Examples of conductive materials that may be included as optional components in the positive electrode active material layer include carbon nanotubes (CNTs), carbon fibers other than CNTs, and conductive particles (e.g., carbon black, graphite).

[0061] [Negative electrode] The negative electrode includes at least a negative electrode current collector. The negative electrode includes, for example, a negative electrode current collector and a negative electrode active material layer. The negative electrode active material layer is supported on one or both surfaces of the negative electrode current collector.

[0062] The negative electrode active material layer may be a negative electrode mixture layer composed of a negative electrode mixture. The negative electrode mixture layer is in the form of a film or membrane. The negative electrode mixture contains particles of the negative electrode active material as an essential component and may contain binders, conductive agents, thickeners, etc. as optional components. Alternatively, lithium metal foil or lithium alloy foil may be attached to the negative electrode current collector as the negative electrode active material layer.

[0063] The negative electrode mixture layer can be formed, for example, by dispersing a negative electrode slurry containing particles of negative electrode active material, a binder, etc., in a dispersion medium onto the surface of the negative electrode current collector and drying it. The dried coating may be rolled if necessary.

[0064] The negative electrode active material includes materials that electrochemically intercalate and release lithium ions, lithium metals, lithium alloys, etc. Examples of electrochemically intercalating and releasing lithium ions include carbon materials and alloying materials. Examples of carbon materials include graphite, easily graphitizable carbon (soft carbon), and poorly graphitizable carbon (hard carbon). Among these, graphite is preferred due to its excellent charge-discharge stability and low irreversible capacity. Examples of alloying materials include those containing at least one metal capable of alloying with lithium, specifically silicon, tin, silicon alloys, tin alloys, and silicon compounds. Silicon oxide, tin oxide, and other silicon-containing materials may also be used.

[0065] Non-porous conductive substrates (such as metal foil) and porous conductive substrates (such as mesh, nets, and perforated sheets) are used as negative electrode current collectors. Examples of materials for negative electrode current collectors include stainless steel, nickel, nickel alloys, copper, and copper alloys.

[0066] For example, styrene-butadiene rubber can be used as a binder, but it is not particularly limited.

[0067] Examples of conductive materials include carbon nanotubes (CNTs), carbon fibers other than CNTs, and conductive particles (e.g., carbon black, graphite).

[0068] Examples of thickening agents include carboxymethylcellulose (CMC) and its modified forms (including salts such as sodium salts), cellulose derivatives such as methylcellulose (such as cellulose ethers); saponified polymers having vinyl acetate units such as polyvinyl alcohol; and polyethers (such as polyalkylene oxides like polyethylene oxide).

[0069] [Separator] A separator is interposed between the positive and negative electrodes. The separator has high ion permeability and appropriate mechanical strength and insulating properties. Examples of separators include microporous thin films, woven fabrics, and nonwoven fabrics. Polyolefins such as polypropylene and polyethylene can be used as materials for the separator. The separator may have a heat-resistant insulating layer on at least one surface layer. The heat-resistant insulating layer may contain inorganic oxide fillers as the main component (e.g., 80% by mass or more) or a heat-resistant resin as the main component (e.g., 40% by mass or more). The heat-resistant resin may be polyamide resin such as aromatic polyamide (aramid), polyimide resin, or polyamide-imide resin.

[0070] [Electrolytes] The electrolyte may be a liquid electrolyte (electrolyte solution), a gel electrolyte, or a solid electrolyte. The gel electrolyte may contain a lithium salt and a matrix polymer, or a lithium salt, a non-aqueous solvent, and a matrix polymer. As the matrix polymer, for example, a polymer material that absorbs a non-aqueous solvent and gels can be used. Examples of polymer materials include fluororesins, acrylic resins, polyether resins, polyethylene oxides, etc.

[0071] The solid electrolyte may be an inorganic solid electrolyte. As an inorganic solid electrolyte, for example, materials known for use in all-solid-state lithium-ion secondary batteries, etc. (e.g., oxide-based solid electrolytes, sulfide-based solid electrolytes, halide-based solid electrolytes, etc.) can be used. The electrolyte may be, for example, a non-aqueous electrolyte containing a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. The concentration of the lithium salt in the non-aqueous electrolyte is, for example, 0.5 mol / L or more and 2 mol / L or less. The non-aqueous electrolyte may contain known additives.

[0072] Examples of non-aqueous solvents include cyclic carbonate esters, linear carbonate esters, and cyclic carboxylic acid esters. Examples of cyclic carbonate esters include propylene carbonate (PC) and ethylene carbonate (EC). Examples of linear carbonate esters include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of cyclic carboxylic acid esters include γ-butyrolactone (GBL) and γ-valerolactone (GVL). Non-aqueous solvents may be used individually or in combination of two or more.

[0073] Examples of lithium salts include lithium salts of chlorine-containing acids (LiClO4, LiAlCl4, LiB 10 Cl 10 Examples include lithium salts of fluorine-containing acids (LiPF6, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts of fluorine-containing acid imides (LiN(SO2F)2, LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), and lithium halides (LiCl, LiBr, LiI, etc.). Lithium salts may be used individually or in combination of two or more types.

[0074] One example of a secondary battery structure is one in which an electrode group, consisting of a positive electrode and a negative electrode wound around a separator, is housed together with an electrolyte in an outer casing. However, the structure is not limited to this, and other forms of electrode groups may be used. For example, a laminated electrode group in which the positive electrode and negative electrode are stacked with a separator in between may also be used. The form of the secondary battery is also not limited; for example, it may be cylindrical, prismatic, coin-type, button-type, laminate-type, etc.

[0075] The structure of the secondary battery will be described below with reference to Figure 1. Figure 1 is a longitudinal cross-sectional view of a cylindrical non-aqueous secondary battery 10, which is an example of this embodiment. However, this disclosure is not limited to the following configuration.

[0076] The secondary battery 10 comprises an electrode group 18, an electrolyte (not shown), and a bottomed cylindrical battery case 22 that houses these. A sealing body 11 is crimped and fixed to the opening of the battery case 22 via a gasket 21. This seals the inside of the battery. The sealing body 11 comprises a valve body 12, a metal plate 13, and an annular insulating member 14 interposed between the valve body 12 and the metal plate 13. The valve body 12 and the metal plate 13 are connected to each other at their respective centers. A positive electrode lead 15a, which is led out from the positive electrode plate 15, is connected to the metal plate 13. Therefore, the valve body 12 functions as an external terminal of the positive electrode. A negative electrode lead 16a, which is led out from the negative electrode plate 16, is connected to the inner surface of the bottom of the battery case 22. An annular groove 22a is formed near the open end of the battery case 22. A first insulating plate 23 is positioned between one end face of the electrode group 18 and the annular groove 22a. A second insulating plate 24 is positioned between the other end face of the electrode group 18 and the bottom of the battery can 22. The electrode group 18 is formed by winding a positive electrode plate 15 and a negative electrode plate 16 with a separator 17 in between.

[0077] The present disclosure will be described in detail below based on examples and comparative examples, but the present disclosure is not limited to the following examples.

[0078] Example 1 [Fabrication of the positive electrode] The positive electrode active material constituting the active material particles is a composite oxide N(LiNi) with an average particle diameter of 13 μm. 0.85 Co 0.10 Al 0.05 O2 was used. In addition, a 15 μm thick aluminum foil was prepared as the positive electrode current collector.

[0079] A cathode slurry was prepared by adding NMP to a cathode mixture containing active material particles, acetylene black, and polyvinylidene fluoride (PVDF) in a mass ratio of 95:2.5:2.5, and 3-acetamidobenzoic acid (average particle size 100 μm) at a content of 1.3% by mass. The mixture was then stirred. During this process, the stirring conditions were controlled so that the particle size of the 3-acetamidobenzoic acid was in the range of 10 μm to 50 μm.

[0080] A positive electrode slurry was applied to the surface of an aluminum foil, which serves as the positive electrode current collector, and the coating was dried to form an unrolled layer on both sides of the aluminum foil. At this time, the drying temperature was controlled to 200°C so that the distribution of 3-acetamidobenzoic acid in the positive electrode active material layer, described later, was Pt / Pb ≈ 1.5.

[0081] Next, the unrolled layer is rolled until the density of the positive electrode active material reaches 3.6 g / cm³. 3 A positive electrode active material layer was formed. The total thickness of the positive electrode after rolling was 160 μm.

[0082] [Fabrication of the negative electrode] A negative electrode slurry was prepared by adding water to a negative electrode mixture containing graphite (the negative electrode active material), sodium carboxymethylcellulose (CMC-Na), and styrene-butadiene rubber (SBR) in a mass ratio of 96:2:2, and stirring. Next, the negative electrode slurry was applied to the surface of a copper foil, which was the negative electrode current collector. After the coating was dried, the foil was rolled to form negative electrode active material layers on both sides of the copper foil. The density of the negative electrode active material in the negative electrode active material layer was 1.6 g / cm³. 3 The adjustments were made to achieve this. The total thickness of the negative electrode was 170 μm.

[0083] [Preparation of non-aqueous electrolytes] A non-aqueous electrolyte was prepared by dissolving LiPF6 at a concentration of 1.0 mol / L in a mixed solvent containing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 3:7.

[0084] [Manufacturing of secondary batteries] An electrode group was fabricated by attaching tabs to each electrode and spirally winding the positive and negative electrodes via a separator so that the tabs were located on the outermost periphery. The electrode group was inserted into an aluminum laminate film casing, vacuum-dried at 105°C for 2 hours, then electrolyte was injected, and the opening of the casing was sealed to obtain secondary battery A1.

[0085] Example 2 Secondary battery A2 was fabricated in the same manner as in Example 1, except that the drying temperature was controlled to room temperature so that the distribution of 3-acetamidobenzoic acid in the positive electrode active material layer satisfies Pt / Pb ≈ 1.

[0086] Example 3 Secondary battery A3 was prepared in the same manner as in Example 1, except that 3-acetamidobenzoic acid was completely dissolved in NMP beforehand when preparing the positive electrode slurry. Specifically, 3-acetamidobenzoic acid in an amount equivalent to 1.3% by mass of the positive electrode mixture was added to NMP at 50°C and dissolved over 3 hours. Then, active material particles, acetylene black, and polyvinylidene fluoride (PVDF) were added to the NMP solution of 3-acetamidobenzoic acid in a mass ratio of 95:2.5:2.5, stirred, and prepared the positive electrode slurry. The drying temperature was controlled to 200°C so that the distribution of 3-acetamidobenzoic acid in the positive electrode active material layer was Pt / Pb ≈ 1.5.

[0087] Example 4 Secondary battery A4 was fabricated in the same manner as in Example 3, except that the drying temperature was controlled to room temperature so that the distribution of 3-acetamidobenzoic acid in the positive electrode active material layer satisfies Pt / Pb ≈ 1.

[0088] Comparative Example 1 Secondary battery B1 was prepared in the same manner as in Example 1, except that 3-acetamidobenzoic acid was not included in the positive electrode mixture (the content of 3-acetamidobenzoic acid was 0%).

[0089] [Rating 1] The secondary batteries obtained in Examples 1-4 and Comparative Example 1 were evaluated as follows. (a) At 25°C, the battery was charged with a constant current of 0.3It until the voltage reached 4.2V, and then charged with a constant voltage of 4.2V until the current reached 0.05It. (b) In an environment of 25°C, the tip of a round nail (2.7 mm in diameter) was brought into contact with the center of the battery charged in (a), and pierced at a speed of 1 mm / second. The piercing of the round nail was stopped immediately after detecting the battery voltage drop (Δ50 mV) due to an internal short circuit. The surface temperature of the battery was measured 1 minute after the battery short-circuited. The surface temperatures of batteries A1 to A4 and battery B1 are shown in Table 1.

[0090] [Table 1]

[0091] Table 1 shows that batteries A1 to A4, compared to battery B1, demonstrated improved safety in the event of an internal short circuit. Furthermore, when comparing examples with the same Pt / Pb value, the improvement in safety is particularly pronounced when particles or aggregates of 3-acetamidobenzoic acid larger than 10 μm are included in the positive electrode active material layer.

[0092] Example 5 Secondary battery A4 was fabricated in the same manner as in Example 1, except that the pyrolytic additive was changed from 3-acetamidobenzoic acid to 4-acetamidobenzoic acid (average particle size 100 μm), and the drying temperature was controlled so that the distribution of 4-acetamidobenzoic acid in the positive electrode active material layer was Pt / Pb ≈ 1.35.

[0093] Example 6 Secondary battery A6 was prepared in the same manner as in Example 2, except that the pyrolytic additive was changed from 3-acetamidobenzoic acid to 4-acetamidobenzoic acid (average particle size 100 μm).

[0094] Example 7 Secondary battery A7 was fabricated in the same manner as in Example 3, except that the pyrolytic additive was changed from 3-acetamidobenzoic acid to 4-acetamidobenzoic acid, and the drying temperature was controlled so that the distribution of 4-acetamidobenzoic acid in the positive electrode active material layer was Pt / Pb ≈ 1.35.

[0095] Example 8 Secondary battery A8 was prepared in the same manner as in Example 4, except that the pyrolytic additive was changed from 3-acetamidobenzoic acid to 4-acetamidobenzoic acid. [Rating 2] The secondary batteries obtained in Examples 5-8 were evaluated in the same manner as in Evaluation 1. The surface temperatures of batteries A5-A8 are shown in Table 2.

[0096] [Table 2]

[0097] Table 2 shows that batteries A5 to A8, compared to battery B1 in Table 1, demonstrated improved safety in the event of an internal short circuit. Furthermore, when comparing examples with the same Pt / Pb value, the improvement in safety is particularly pronounced when 4-acetamidobenzoic acid particles or aggregates larger than 10 μm are included in the positive electrode active material layer. Tables 1 and 2 also show that 3-acetamidobenzoic acid has a greater safety-enhancing effect than 4-acetamidobenzoic acid. [Industrial applicability]

[0098] The positive electrode for secondary batteries and secondary batteries containing the same relating to this disclosure are useful as primary power sources for mobile communication devices, portable electronic devices, electric vehicles, and the like.

[0099] Although the present invention has been described in relation to preferred embodiments at present, such disclosure should not be interpreted restrictively. Various modifications and alterations will undoubtedly become apparent to those skilled in the art in the field to which the invention pertains by reading the above disclosure. Accordingly, the appended claims should be interpreted as encompassing all modifications and alterations without departing from the true spirit and scope of the invention. [Explanation of symbols]

[0100] 10: Secondary battery, 11: Sealing body, 12: Valve body, 13: Metal plate, 14: Insulating material, 15: Positive electrode plate, 15a: Positive electrode lead, 16: Negative electrode plate, 16a: Negative electrode lead, 17: Separator, 18: Electrode group, 21: Gasket, 22: Battery can, 22a: Groove, 23: First insulating plate, 24: Second insulating plate

Claims

1. It comprises a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector, The positive electrode active material layer comprises active material particles, a binder, and a thermally decomposable additive. The aforementioned pyrolytic additive contains acetamidebenzoic acid, and is a positive electrode for a secondary battery.

2. The positive electrode for a secondary battery according to claim 1, wherein at least a portion of the pyrolytic additive is present in the positive electrode active material layer as particles having a particle size of 10 μm or more.

3. The positive electrode for a secondary battery according to claim 2, wherein, in cross-sectional observation of the positive electrode active material layer, five or more particles of the pyrolytic additive with a particle diameter of 10 μm or more are observed in a rectangular observation field defined by a length of 300 μm in the planar direction of the positive electrode active material layer × the thickness of the positive electrode active material layer.

4. The positive electrode for a secondary battery according to any one of claims 1 to 3, wherein the content of acetamidobenzoic acid in the positive electrode active material layer is 0.1% by mass or more and 5% by mass or less.

5. The positive electrode for a secondary battery according to any one of claims 1 to 3, wherein when the cross-section of the positive electrode active material layer is analyzed with a scanning electron microscope and an electron beam microanalyzer, the area of ​​the region where acetamidobenzoic acid is present is 0.5 area % or more and 27 area % or less in a rectangular observation field defined by a length of 300 μm in the planar direction of the positive electrode active material layer and the thickness T of the positive electrode active material layer.

6. The positive electrode for a secondary battery according to any one of claims 1 to 3, wherein the thermally decomposable additive contains 500 μg to 5000 μg of acetic acid component per gram.

7. The positive electrode for a secondary battery according to any one of claims 1 to 3, wherein the pyrolytic additive coats a portion of the surface of the active material particles.

8. The aforementioned pyrolytic additive is predominantly located on the outermost surface side of the earlier positive electrode active material layer, rather than on the earlier positive electrode current collector side. When the thickness of the positive electrode active material layer is T, The probability Pb ​​of the presence of the pyrolytic additive in the region from the surface of the positive electrode current collector in the positive electrode active material layer up to 0.5T, The positive electrode for a secondary battery according to any one of claims 1 to 3, wherein the probability Pt of the presence of the pyrolytic additive in the region of the positive electrode active material layer from a position 0.5T from the surface of the positive electrode current collector to the outermost surface satisfies 1.35 ≤ Pt / Pb.

9. The active material particles include a lithium-containing transition metal oxide. Lithium-containing transition metal oxides include lithium nickel oxide, which contains lithium and Ni and has a layered rock salt-type crystalline structure. The positive electrode for a secondary battery according to any one of claims 1 to 3, wherein the proportion of Ni among the metal elements other than Li contained in the lithium nickel oxide is 50 atomic percent or more.

10. The lithium nickel oxide is Formula: Li α Ni x1 M1 x2 M2 (1-x1-x2) O 2+β It is represented as, Element M1 is at least one selected from the group consisting of V, Co, and Mn. Element M2 is at least one selected from the group consisting of Mg, Al, Ca, Ti, Cu, Zn, and Nb. 0.95≦α≦1.05、 -0.05≦β≦0.05、 0.5 ≤ x 1 < 1, 0 ≤ x² ≤ 0.5, 0<1-x1-x2≦0.5 A positive electrode for a secondary battery according to claim 9, satisfying the requirements.

11. The positive electrode for a secondary battery according to any one of claims 1 to 3, wherein the binder is at least one selected from the group consisting of fluororesin and hydrogenated nitrile butadiene rubber.

12. A secondary battery comprising a positive electrode, a negative electrode, a lithium-ion conductive electrolyte, and a separator interposed between the positive electrode and the negative electrode, as described in any one of claims 1 to 3.

13. A step of preparing a positive electrode slurry containing active material particles, a binder, a thermally decomposable additive, and a dispersion medium, The process of preparing the positive electrode current collector, A step of applying the positive electrode slurry to the surface of the positive electrode current collector to form a coating film, The process involves drying the aforementioned coating to form an unrolled layer, The process involves rolling the aforementioned unrolled layer to form a positive electrode active material layer, It is equipped with, The aforementioned pyrolytic additive contains acetamidebenzoic acid, A method for manufacturing a positive electrode for a secondary battery, wherein the dispersion medium contains an organic solvent.

14. The method for manufacturing a positive electrode for a secondary battery according to claim 13, wherein at least a portion of the pyrolytic additive is present in the positive electrode slurry as particles having a particle size of 10 μm or more.

15. When the thickness of the positive electrode active material layer is T, The probability Pb ​​of the presence of the pyrolytic additive in the region from the surface of the positive electrode current collector in the positive electrode active material layer up to 0.5T, The probability Pt of the presence of the pyrolytic additive in the region of the positive electrode active material layer from a position 0.5T from the surface of the positive electrode current collector to the outermost surface is such that 1.35 ≤ Pt / Pb. A method for manufacturing a positive electrode for a secondary battery according to claim 13 or 14, wherein in the step of drying the coating film to form an unrolled layer, the coating film is dried at a temperature of 150°C or higher.

Citation Information

Patent Citations

  • High-specific-energy and high-safety lithium ion power battery based on high-nickel ternary material

    CN105609869A

  • Positive electrode active material and lithium secondary battery using it

    JP2000315502A

  • Positive electrode plate and nonaqueous electrolyte secondary battery

    JP2019075222A

  • Electrochemical element electrode, electrochemical element, and manufacturing method for electrochemical element electrode

    WO2019021891A1